Clinical Implications of Monogenic Versus Polygenic Hypercholesterolemia: Long‐Term Response to Treatment, Coronary Atherosclerosis Burden, and Cardiovascular Events - Laura D’Erasmo; Ilenia Minicocci; Alessia Di Costanzo; Giovanni Pigna; Daniela Commodari; Fabrizio Ceci; Anna Montali; Francesca Brancato; Ilaria Stanca; Antonio Nicolucci; Andrea Ascione; Nicola Galea; et al. (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease, 2021)
Background Familial hypercholesterolemia (FH) may arise from deleterious monogenic variants in FH‐causing genes as well as from a polygenic cause. We evaluated the relationships between monogenic FH and polygenic hypercholesterolemia in influencing the long‐term response to therapy and the risk of atherosclerosis. Methods and Results A cohort of 370 patients with clinically diagnosed FH were screened for monogenic mutations and a low‐density lipoprotein‐rising genetic risk score >0.69 to identify polygenic cause. Medical records were reviewed to estimate the response to lipid‐lowering therapies and the occurrence of major atherosclerotic cardiovascular events during a median follow‐up of 31.0 months. A subgroup of patients (n=119) also underwent coronary computed tomographic angiography for the evaluation of coronary artery calcium score and severity of coronary stenosis as compared with 135 controls. Two hundred nine (56.5%) patients with hypercholesterolemia were classified as monogenic (FH/M+), 89 (24.1%) as polygenic, and 72 (19.5%) genetically undefined (FH/M−). The response to lipid‐lowering therapy was poorest in monogenic, whereas it was comparable in patients with polygenic hypercholesterolemia and genetically undetermined. Mean coronary artery calcium score and the prevalence of coronary artery calcium >100 units were significantly higher in FH/M+ as compared with both FH/M− and controls. Finally, after adjustments for confounders, we observed a 5‐fold higher risk of incident major atherosclerotic cardiovascular events in FH/M+ (hazard ratio, 4.8; 95% CI, 1.06–21.36; Padj=0.041). Conclusions Monogenic cause of FH is associated with lower response to conventional cholesterol‐lowering therapies as well as with increased burden of coronary atherosclerosis and risk of atherosclerotic‐related events. Genetic testing for hypercholesterolemia is helpful in providing important prognostic information.